2023
DOI: 10.1002/adma.202302552
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ion Migration for Highly Efficient and Stable Perovskite Solar Cells

Abstract: In recent years, organic‐inorganic halide perovskites are now emerging as the most attractive alternatives for next‐generation photovoltaic devices, due to their excellent optoelectronic characteristics and low manufacturing cost. However, the resultant perovskite solar cells (PVSCs) are intrinsically unstable owing to ion migration, which severely impedes performance enhancement, even with device encapsulation. There is no doubt that the investigation of ion migration and the summarization of recent advances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 335 publications
(839 reference statements)
1
13
0
Order By: Relevance
“…[40] All these interactions between TB and perovskite precursor will retard the crystallization process of perovskite film. [12,41] This is expected to greatly improve the performance and stability of PSCs.…”
Section: Resultsmentioning
confidence: 99%
“…[40] All these interactions between TB and perovskite precursor will retard the crystallization process of perovskite film. [12,41] This is expected to greatly improve the performance and stability of PSCs.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of mobile ions in metal halide perovskites of different compositions has been well established and linked to hysteresis and device (in)­stability. Although there is still debate about exactly which ions are moving and how high the corresponding mobile ion densities are, the important role that mobile ions play in PSCs is generally well recognized (Figure ). In addition to causing phase instabilities and chemical decomposition of the perovskite, mobile ions can influence the performance of PSCs by altering their electronic properties.…”
Section: Origins Of Efficiency Lossesmentioning
confidence: 99%
“…Ion migration is a common phenomenon in the entire device of PSC. 83 In particular, atoms or groups in the perovskite at the interface can move in a disordered manner. 84 Numerous studies have demonstrated that ions (such as MA + or I − ) in perovskite materials show a low activation barrier and a modest ionic diffusion coefficient to move within perovskite devices, particularly under external bias or illumination.…”
Section: The Importance Of Interface Engineeringmentioning
confidence: 99%